Pembinaan Pengemis di Kota Bandung Berdasarkan Perda Nomor 9 Tahun 2019 Ditinjau dari Siyasah Dusturiyah - Amelia, Putri; Shaleh, Chaerul; Rizal, Lutfi Fahrul (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
Poverty has been a persistent problem in Indonesia since before its establishment as a nation, making it a complex and longstanding issue. Numerous studies have explored the causes of poverty and proposed solutions; however, the implementation of these solutions remains suboptimal. Urban poverty, exacerbated by the impact of development, is particularly evident in metropolitan cities, including Bandung. This contradicts the fundamental goal of development, which is to enhance community welfare. Bandung faces significant challenges with the presence of beggars and vagrants, despite the enactment of Regional Regulation Number 9 of 2019 concerning Public Order. The regulation's sanctions have proven ineffective, and current empowerment programs often prioritize material assistance over fostering community independence, leading to dependency. This study aims to identify the root causes of poverty in Bandung, evaluate existing government programs, and propose more effective strategies for empowering beggars and vagrants. Using a qualitative descriptive method, data were collected through interviews, observations, and document analysis. The findings reveal that key factors contributing to poverty include low education levels, inadequate skills, and lack of motivation. Government efforts in training and social rehabilitation are essential for reintegrating individuals into society and promoting self-reliance. The study concludes that addressing poverty and the challenges faced by beggars and vagrants in Bandung requires a comprehensive and integrated approach involving government policies and active community participation. This research contributes to the discourse on urban poverty alleviation by highlighting the importance of sustainable empowerment programs that focus on building independence rather than dependency